1999
DOI: 10.1097/00055735-199904000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma drainage devices: pros and cons

Abstract: Glaucoma drainage devices are an option in the management of complicated glaucomas that carry a high risk of failure from conventional filtering surgery. Examples include the glaucomas associated with aphakia or pseudophakia, neovascular glaucoma, and glaucomas associated with trauma, uveitis, epithelial downgrowth, iridocorneal endothelial syndrome, vitreoretinal disorders, and penetrating keratoplasty. Modifications in the various implant designs have been developed to limit the occurrence of postsurgical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 35 publications
1
42
0
1
Order By: Relevance
“…AGV consists of three parts: (1) a plate which, depending on the model, is composed of medical grade silicone, polypropylene or polyethylene (Medpor; Porex, Atlanta, GA, USA; subsequently Stryker, Kalamazoo, MI, USA), (2) a drainage tube composed of medical grade silicone, and (3) a valve mechanism made of medical-grade silicone (Fig. 1a).…”
Section: Ahmed Glaucoma Valve: Device Description and Technical Datamentioning
confidence: 99%
See 2 more Smart Citations
“…AGV consists of three parts: (1) a plate which, depending on the model, is composed of medical grade silicone, polypropylene or polyethylene (Medpor; Porex, Atlanta, GA, USA; subsequently Stryker, Kalamazoo, MI, USA), (2) a drainage tube composed of medical grade silicone, and (3) a valve mechanism made of medical-grade silicone (Fig. 1a).…”
Section: Ahmed Glaucoma Valve: Device Description and Technical Datamentioning
confidence: 99%
“…The adult model (S2) of AGV provides 184 mm 2 of total plate area, while the pediatric model (S3) provides a total area of 96 mm 2 . Obviously, a smaller plate facilitates positioning in infants and subjects with a small eye.…”
Section: Ahmed Glaucoma Valve: Device Description and Technical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…While these methods are successful in lowering IOP, long-term visual acuity outcomes have been variable. [12][13][14][15][16][17][18][19][20] Inhibition of VEGF-A by bevacizumab has been shown to be successful in causing short-term regression of retinal neovascularization. Recently, intravitreal injection of this agent has demonstrated rapid regression of neovascularization of the iris (NVI).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigators have reported a high incidence of corneal graft failure, varying between 20 and 50% after drainage tube insertion for the treatment of glaucoma. [6][7][8] The presence of a glaucoma drainage device was considered by many to be associated with a worse prognosis for graft survival, 6,7,9-11 and a significant and independent risk factor for corneal graft failure. 12 The mechanism for graft failure in these patients is not fully understood.…”
Section: Introductionmentioning
confidence: 99%